Recycling of carbon fibre via pyrolysis technologies - Hao, Siqi (2021)
Carbon fibre reinforced plastic (CFRP) composites have been widely used in many industrial fields, such as the automotive and aviation industries, due to their impressive properties including being lightweight, corrosion-resistant and having a high strength to weight ratio. This inevitably generates large amounts of composites waste during the manufacturing process and when these composite products reach the end of their service life. Considering the environmental and economic impact, composites recycling has become one of the top priorities for composite industries. Currently the main recycling techniques that have been developed include mechanical recycling, chemical solvolysis and pyrolysis. Among all these, pyrolysis has been proven to be the most promising recycling technique. This study focuses on pyrolysis techniques, further optimizes and develops pyrolysis methods including conventional pyrolysis, hybrid pyrolysis method and microwave pyrolysis from the aspect of char elimination, so that a higher quality carbon fibre can be recovered with a potential for energy saving. At the beginning of the study, an optimization of conventional pyrolysis was conducted to reduce the char formation via the thermal analysis of two types carbon fibre thermoset composite. The effect of pyrolytic conditions, in terms of heating rate, pyrolysis temperature and inert gas flow rate on char retention and intrinsic reactivity were investigated. It was found the pyrolytic char formation reduced as the heating rate, pyrolysis temperature, and gas flow rate increased, whilst the char intrinsic reactivity increased with fast heating rate and low temperature. The improvement in intrinsic reactivities were attributed to the rise in oxygen-to-carbon ratio, char pore size, and BET surface area. A more porous structure was observed from the char generated from a fast heating rate and high temperature. This consolidated the effect of pyrolytic conditions on the char intrinsic reactivity. This research confirmed that the appropriate selection of pyrolytic reaction conditions not only reduces the char yield, but also improves the char oxidation activity. Secondly, a new hybrid recycling approach was developed to reduce char formation significantly using a combination of a chemical pre-treatment followed by a conventional pyrolysis process. Zinc chloride/ethanol solution was selected as the pre-treatment agent. After immersing carbon fibre epoxy prepreg in the 40 wt.% ZnCI2/C2H5OH solution at 80 °C for 2 hours, some tiny cracks appeared on the surface of the prepreg and the required pyrolysis temperature reduced. The surface morphology and chemistry, mechanical performance of recycled carbon fibre have been investigated. The recycled carbon fibres retained a competitive mechanical performance closed to virgin carbon fibre and appeared to have a relatively clean surface with small residues. As compared with the standard pyrolysis recycling process, this hybrid method results in carbon fibre with higher mechanical performance. Finally, the utilisation of microwave pyrolysis was attempted in a multi-mode microwave reactor to potentially improve the pyrolysis efficiency. The pyrolytic products distributions and properties of carbon fibre epoxy prepreg pyrolyzed at different microwave temperatures of 450 °C, 550 °C and 650 °C were investigated. It was found that higher temperatures resulted in less char formation and a higher yield of gas and liquid products. The carbon fibre recovered at 450 °C showed the highest tensile strength, while there was no significant change in tensile modulus for carbon fibre extracted at different microwave temperatures. The recycled carbon fibre showed a relatively clean surface, with increasing number of oxygen-containing groups. The gas released from the process has a composition of H2, CO and CO2, and the major liquid product components are phenols and aromatics. The microwave pyrolysis has demonstrated a potential as a low energy consuming method of carbon fibre pyrolysis recycling. In summary, carbon fibre was successfully recycled from a carbon fibre composite using various pyrolysis technologies in this research. The optimization and development of these pyrolysis technologies have the potential not only to reduce or eliminate the char formation, but also to recover high-quality fibre and save thermal energy.